Biodegradation of empty fruit bunch (EFB) in liquid fermentation using mixed microbes from palm oil mill effluent (POME): effect of aeration rate - Abd. Halim, Nor Fadilah; Tey, Beng Ti; Masduki, Suhaimi (Malaysian Agricultural Research and Development Institute (MARDI), 2009)
The biodegradation of oil palm empty fruit bunch (EFB) in liquid fermentation using microorganism complex obtained from palm oil mill effluent (POME) under non-axenic condition was studied. A parallel study on carboxyl methyl cellulose (CMC) as substrate was also conducted as a comparison. The effects of the operating parameters of fermentation, aeration rates on the degradation of EFB and CMC were studied. The degradation was performed at agitation speed of 150 rpm in a 10 litre bioreactor under process parameter for a 10 day period. The evolution of dry matter (DM) and chemical oxygen demand of solids (CODs) were used to measure the performance of the non-sterile liquid fermentation process on the solid degradation of EFB and CMC. The effect of aeration rate on the reduction of DM and CODs differs. For EFB, a 10 fold increase in DM reduction was observed when the aeration rate was raised from 0 to 1.0 vvm. On the other hand, the increase in DM reduction of CMC was lower than that of EFB as a result of the increased aeration rate. The highest CODs reduction for EFB (64.82%) and CMC (20.2%) was achieved at aeration rate of 0.5 vvm. Aeration rate of 0.5 vvm was selected as the rate for optimum biodegradation.